2012
DOI: 10.1111/j.1753-0407.2011.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscular strengthening activity patterns and metabolic health risk among US adults*

Abstract: Background-Many studies have examined the relationship between physical activity and metabolic disorders. However, few have focused on specific associations between these disorders and muscular strengthening activity (MSA) patterns. The aim of the present study was to examine the association(s) for each metabolic syndrome criterion and MSA patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…(response option: yes or no), and 2) among those answering yes to this first question, they were asked, "Over the past 30 days, how many times did you do these activities designed to strengthen your muscles such as lifting weights, push-ups, or sit-ups?" These NHANES MSA items have provided some evidence of construct validity (e.g., shown to associate with metabolic syndrome) (Churilla et al, 2012).…”
Section: Measurement Of Muscle Strengthening Activitiesmentioning
confidence: 99%
“…(response option: yes or no), and 2) among those answering yes to this first question, they were asked, "Over the past 30 days, how many times did you do these activities designed to strengthen your muscles such as lifting weights, push-ups, or sit-ups?" These NHANES MSA items have provided some evidence of construct validity (e.g., shown to associate with metabolic syndrome) (Churilla et al, 2012).…”
Section: Measurement Of Muscle Strengthening Activitiesmentioning
confidence: 99%
“…It has been reported that resistance training appears to prevent metabolic disorders such as dyslipidemia, impaired fasting glucose, pre-hypertension, and increased waist circumference, but not hypertension 37 , while recognizing that increased strength may improve vascular health and reduce complications 38 and mortality among hypertensive individuals 39 . The statistical association between handgrip strength and hypertension may mean that muscle strength expresses overall individual fitness 40 more than a direct relationship with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…12,29 Churilla et al 29 reported a significantly lowered odds (OR: 0.71, 95% CI: 0.54−0.93) for having impaired fasting glucose, potentially suggesting normal β-cell function and better metabolic health in subjects who report meeting the DHHS MSA recommendation compared to subjects reporting no MSA. In another analysis using 1999-2004 NHANES, Cheng et al 12 investigated the associations between MSA and insulin sensitivity (measured via QUICKI 30 ) in euglycaemic subjects.…”
Section: Discussionmentioning
confidence: 99%